Struggling for change in chilean EFL teacher education - Abrahams, Mary Jane; Farias, Miguel (Colombian Applied Linguistics Journal, 2010)
We here report on the processes of designing and trying to implement curriculum innovations in English as a foreign language (EFL) teacher education in Chile. This curriculum innovation project involved academics from six universities where problems such as a divorce between training in English linguistics and education, lack of language achievement standards and students’ low scores in international exams were found to be common to all six EFL teacher education programs. All of this amidst a general opinion (shared by parents, teachers, politicians, etc.) that Chile is immersed in an educational crisis without any easy solution. In this context an urgent need arises for an innovative and very creative design to change the curricula at universities so that the country can raise the quality in foreign language education. The aim is for language education to have a real impact in the school communities. Having Critical Pedagogy as one of the main supporting models, this design we report on is based on the idea that the traditional curriculum is a pedagogy that transmits inflexible social truths; consequently, this proposal incorporates participatory and reflective instructional activities, such as situated and transformed practice and critical framing.